2022
DOI: 10.1002/adma.202203791
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenization of Molecular Electrocatalytic Active Sites through Reticular Chemistry

Abstract: The electrochemical conversion of small molecules, such as CO2, O2, and H2O, has received significant attention as a potential engine for sustainable life. Metal–organic frameworks (MOFs) are a promising class of electrocatalytic materials for such processes. An attractive aspect of utilizing this class of materials as electrocatalysts is that well‐known molecular active sites can be introduced to well‐defined crystalline heterogeneous catalytic systems with high tunability. This review offers strategic insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 170 publications
(163 reference statements)
0
9
0
Order By: Relevance
“…25 These entail molecules adsorbed, grafted, or grown on heterogeneous electrodes, 13 as well as MOFs/COFs deposited/grown on electrode surfaces. 26–28 Heterogenized molecular systems have advantages since their active sites are ‘wired’ to the electrode the entire time while still being accessible to reactants in the electrolyte, a situation more closely resembling heterogeneous material electrocatalysts. One key additional parameter is the link between the catalyst and electrode, which plays a determining role in stability (minimizing desorption) and activity (facilitating electron transfer).…”
Section: Introductionmentioning
confidence: 99%
“…25 These entail molecules adsorbed, grafted, or grown on heterogeneous electrodes, 13 as well as MOFs/COFs deposited/grown on electrode surfaces. 26–28 Heterogenized molecular systems have advantages since their active sites are ‘wired’ to the electrode the entire time while still being accessible to reactants in the electrolyte, a situation more closely resembling heterogeneous material electrocatalysts. One key additional parameter is the link between the catalyst and electrode, which plays a determining role in stability (minimizing desorption) and activity (facilitating electron transfer).…”
Section: Introductionmentioning
confidence: 99%
“…55 The tunability and spatial arrangement of MOF structures make it possible for them to introduce various active species to achieve high catalytic activity. 56 Recent studies have revealed that the surface of MOFs undergoes reconstruction in the OER process to form metal hydroxides/oxyhydroxides with abundant defects that are induced by the porous structure and the presence of ligands in MOFs. 57−59 This makes MOFs a promising class of pre-electrocatalysts for the OER.…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic–organic combination of MOFs can generate infinite possibilities, giving them characteristics such as adjustable pores, ultrahigh specific surface area, controllable composition, and diverse coordination modes. Especially, benefiting from the high density of metal active sites, the pristine MOFs with diverse MO 6 -based inorganic units have shown great potential in electrocatalysis . The tunability and spatial arrangement of MOF structures make it possible for them to introduce various active species to achieve high catalytic activity . Recent studies have revealed that the surface of MOFs undergoes reconstruction in the OER process to form metal hydroxides/oxyhydroxides with abundant defects that are induced by the porous structure and the presence of ligands in MOFs. This makes MOFs a promising class of pre-electrocatalysts for the OER.…”
Section: Introductionmentioning
confidence: 99%
“…For the last three decades, traditional metal-ligand coordination chemistry has expanded the research area to coordination polymers with diverse topologies by employing linker ligand building blocks achieving huge progress both in scientific and technological applications by virtue of the new materials. [1][2][3][4][5][6][7][8] Of these, one-dimensional (1D) coordination polymers are the most fundamental in topologies. 2,9 Thus, the synthetic research for the 1D coordination polymers could be considered less interesting structurally even though diverse types of related nanomaterials including nanowires, nanotubes, nanorods, etc.…”
Section: Introductionmentioning
confidence: 99%